The localized instability of the elastic plate-strip streamlined by supersonic gas flow - M. V. Belubekyan; S. R. Martirosyan (National Academy of Sciences of Armenia)
The paper is devoted to the analysis of the divergence localized instability of the elastic plate–strip model in a supersonic gas flow. The critical velocity of the gas flow is found, which reduce to the divergence localized instability arising in the vicinity of free edge of a plate–strip. В предлагаемой работе исследуется локализованная дивергентная неустойчивость, возникающая в окрестности свободного края полубесконечной пластины – полосы при обтекании её сверхзвуковым потоком газа. Ներկայացված աշխատանքում ուսումնասիրված է գերձայնային գազի հոսքում շրջհոսող առաձգական սալի դիվերգենտ անկայունությունը, որը առաջանում է սալի ազատ եզրի շրջակայքում:
Keywords: Mechanics of deformable solids; Coupling of solid mechanics with other effects; Thin bodies, structures